Aspecto radiológico e macroscópico de matriz óssea mineralizada heteróloga fragmentada e polimetilmetacrilato autoclavados em falha óssea de tíbia de coelho - Moreira, Roberto; Dória, Renata G.s.; Camargo, Lázaro M.; Santos, Marcelo D.; Minto, Bruno W. [UNESP]; De Nardi, Andrigo B. [UNESP]; Ambrósio, Carlos E.; Freitas, Silvio H. (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
A segmental defect of 6mm diameter was performed in the medial metaphyseal region of the tibia of 12 rabbits. For the bone defect reconstruction there was implanted a combination of micro and macro fragments of heterologous fragmented cortical bone matrix preserved in glycerin (98%) and polymethylmethacrylate, both autoclaved. Radiological and macroscopic evaluation was performed at 30, 60, 90 and 120 days. Adhesion in relation to time of the micro and macro composites to the recipient bed was observed in 100% of the cases. This showed that this implant is biologically biocompatible, since it promoted bone defects repair, with no signs of infection, migration and/or rejection. In this way, this implant can be classified as one more option of substitute to fill large bone defects.

Foi realizada falha segmentar com 6mm de diâmetro na região metafisária medial de tíbias de 12 coelhos, onde foi implantado uma associação de micro e macrofragmentos de matriz óssea cortical heteróloga fragmentada conservada em glicerina (98%) e polimetilmetacrilato autoclavados, para a sua reconstrução, e avaliados radiológica e macroscopicamente aos 30, 60, 90 e 120 dias. Houve adesão, em relação ao tempo, dos micro e macrocompósitos ao leito receptor, em 100% dos casos, mostrando ser biologicamente biocompatível, pois promoveram a reparação de falhas ósseas, sem sinais de infecção, migração e/ou rejeição, podendo, dessa forma, ser mais uma opção como substituto para preencher grandes defeitos ósseos.
Radiological and macroscopic aspects of autoclaved heterologous fragmented mineralized bone matrix and polymethylmethacrylate in bone defect in tibia of rabbits
Keywords: Biomaterials; Rabbits; bone matrix; osteoconductive; polymethylmethacrylate; Biomateriais; Coelhos; matriz óssea; Osteocondução; polimetilmetacrilato